Effect of Sildenafil Citrate on exercise capacity in athletes with spinal cord injury - Perret, C.; Van Biesen, D.; Strupler, M.; Pit-Grosheide, P.; Vanlandewijck, Y. (International Journal of Sports Physiology and Performance, 2020)
Purpose: Ingestion of sildenafil citrate has performance-enhancing effects at high altitudes above 3800 m in able-bodied individuals. It is unknown whether it can improve the performance of athletes with spinal cord injury (SCI) at moderate altitudes (<2200 m), relevant to Paralympic competitions. As most men with SCI suffer from erectile dysfunction of neurologic origin and use sildenafil on a regular basis, it seems important to study the impact of sildenafil on exercise capacity. The outcome of this study is also relevant to the antidoping community. Methods: Twenty-seven healthy male wheelchair athletes with a motor-complete SCI participated in this prospective double-blind, randomized, placebo-controlled study. The participants performed arm cranking exercise to exhaustion at sea level and moderate altitude (2200 m) after ingestion of 50 mg sildenafil citrate or a placebo. Peak power output, peak oxygen uptake, peak heart rate, rating of perceived exertion, oxygen saturation, and lactate concentrations at exhaustion were measured. Results: Friedman analysis showed that peak power output at sea level was significantly higher (P=.004) under placebo treatment (median [minimum; maximum]: 120 W [35; 170]) compared with sildenafil (115 W [40; 165]). Blood oxygen saturation under sildenafil treatment at sea level (98% [81; 100]) was significantly higher (P=.006) compared with sildenafil treatment at moderate altitude (94% [85; 100]). All other parameters revealed no impact of sildenafil or altitude. Conclusions: In this study, the ingestion of sildenafil citrate in athletes with SCI demonstrated no positive effects on peak arm-cranking-exercise capacity compared with placebo either at sea level or at moderate altitude.